2020
DOI: 10.3390/ani10081414
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidative Effects of Human Adipose Stem Cell Conditioned Medium with Different Basal Medium during Mouse Embryo In Vitro Culture

Abstract: The quality of embryos produced by assisted reproductive techniques should be advanced by the improvement of in vitro culture conditions for successful implantation and pregnancy maintenance. We investigated the anti-oxidative effect of human adipose stem cell (ASC) conditioned medium with its optimal basal medium, Dulbecco′s modified Eagle′s medium (DMEM-CM), or keratinocyte serum-free medium (KSFM-CM) as supplements during in vitro culture (IVC) of in vitro fertilized mouse embryo. At first, preimplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…The rate of embryos that developed to the 4-cell and 16-cell stage were significantly lower in the 50% AMSC-CM group than in the 10% AMSC-CM group. These results indicate that a high CM concentration does not ensure better efficiency of embryo development regardless of the large quantity of cytokines as previously explained [6]. Remarkably, we found that 10% AMSC-CM significantly improved BL formation rate (Table 2), which is an index for embryo developmental potential and consequently determines the success of implantation [41], compared to the control group as well as the other higher concentration of AMSC-CM treated groups.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The rate of embryos that developed to the 4-cell and 16-cell stage were significantly lower in the 50% AMSC-CM group than in the 10% AMSC-CM group. These results indicate that a high CM concentration does not ensure better efficiency of embryo development regardless of the large quantity of cytokines as previously explained [6]. Remarkably, we found that 10% AMSC-CM significantly improved BL formation rate (Table 2), which is an index for embryo developmental potential and consequently determines the success of implantation [41], compared to the control group as well as the other higher concentration of AMSC-CM treated groups.…”
Section: Discussionsupporting
confidence: 63%
“…2019-03). ASCs were cultured and characterized as previously described [ 6 ]. For the establishment of AMSCs, cryopreserved AMSCs (1 × 10 6 ) from the amnion tissue of three female donors were cultured in T-175 flasks containing RPME-P (R BIO, Seoul, Korea) supplemented with 1% antibiotic-antimycotic solution at 37 °C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations